Foreign direct investments and their importance for external economic balance - Havel, Radek (2011)
Foreign direct investments have an important role in current global economy. Their inflow is accelerated by deregulation of financial flows and the globalization of economics. Attractiveness for foreign investments is an integral part of economic policy in small open economy. Inflow of capital has not only the positive effects. The negative ones could be pushing for appreciation of currency or the problem of massive repatriation of profits